Energy metabolism disturbance in migraine: From a mitochondrial point of view - Wang, Yicheng; Wang, Yongli; Yue, Guangxin; Zhao, Yonglie (Frontiers in Physiology, 2023)
Migraine is a serious central nervous system (CNS) disease with a high incidence rate. Its pathogenesis is very complex, which brings great difficulties for clinical treatment. Recently, many studies have revealed that mitochondrial dysfunction may play a key role in migraine, which affects the hyperosmotic of Ca2+, the excessive production of free radicals, the decrease of mitochondrial membrane potential, the imbalance of mPTP opening and closing, and the decrease of oxidative phosphorylation level, which leads to neuronal energy exhaustion and apoptosis, and finally lessens the pain threshold and migraine attack. This article mainly introduces CSD, a pathogenesis of migraine, and then damages the related function of mitochondria, which leads to migraine. Oxidative phosphorylation and the tricarboxylic acid cycle are the main ways to provide energy for the body. 95 percent of the energy needed for cell survival is provided by the mitochondrial respiratory chain. At the same time, hypoxia can lead to cell death and migraine. The pathological opening of the mitochondrial permeability transition pore can promote the interaction between pro-apoptotic protein and mitochondrial, destroy the structure of mPTP, and further lead to cell death. The increase of mPTP permeability can promote the accumulation of ROS, which leads to a series of changes in the expression of proteins related to energy metabolism. Both NO and CGRP are closely related to the attack of migraine. Recent studies have shown that changes in their contents can also affect the energy metabolism of the body, so this paper reviews the above mechanisms and discusses the mechanism of brain energy metabolism of migraine, to provide new strategies for the prevention and treatment of migraine and promote the development of individualized and accurate treatment of migraine.